Constitutional human rights in Vietnam and nordic countries: A comparative analysis - Nguyen, Thi Thanh (Đại học Quốc gia Hà Nội, 2020)
In a democratic, civilized society, human rights become a measurement of human values. Protecting and promoting human rights is an indispensable need, which can be achieved in many ways, with the participation of all members of society. The State plays a pioneering role in ensuring, protecting, and promoting human rights in a strong and effective manner, and this is manifested through its wide scope, covering all legislative, executive, and judiciary activities. Specifically, the constitution, a formal, orthodox form, has the highest legal value of recognizing, guaranteeing, protecting, and promoting human rights. This article focuses on the constitutional study of human rights protection, comparing the Constitution of Nordic (Scandinavian) countries with the Constitution of Vietnam, from historical aspects promulgated and other aspects, such as the development, contribution, and implementation of the Constitution in protecting human rights and for humans rights. The Constitution emphasizes civil, political, or equal rights and prioritizes the laws which recognize and protect human rights. The article also argues that enforcement and defense of the constitution does not necessarily involve a constitutional court. Finally, it has implications on the civilization, rationality, shortcomings, and development orientation of Vietnam’s Constitution on human rights.